Pelatihan Optimalisasi Akun Pembelajaran Bagi Guru - Bahly; Baharman; Sakaria; Muhammad Ilham; Iin Nur Yasinta (PT. Mediatama Zayna Indonesia, 2025)
Digital transformation in education demands teachers' readiness to utilize technology, including digital learning accounts such as belajar.id provided by the government. However, the reality in the field shows that many teachers in rural areas have not optimized these accounts due to limited digital literacy. This service activity aims to improve the competence of SD Negeri No. 28 Inpres Luaor teachers in activating and optimally utilizing learning accounts. The method used includes identification of partner needs, activity planning, training implementation, and evaluation and follow-up. The results showed that all participants were able to activate their learning.id accounts and understand the basic functions of Google Workspace for Education services. This training made the majority of participants able to apply the services contained in the belajar.id account. The training also succeeded in increasing teachers' confidence in using technology and triggering continuous learning initiatives through teacher learning groups. Using a contextual and participatory approach, the training proved effective in empowering teachers in rural school settings to adopt learning technology more actively and sustainably.